The Regulation of Integrated Stress Response Signaling Pathway on Viral Infection and Viral Antagonism - Wu, Yongshu; Zhang, Zhidong; Li, Yanmin; Li, Yijing (Frontiers in Microbiology, 2022)
The integrated stress response (ISR) is an adaptational signaling pathway induced in response to different stimuli, such as accumulation of unfolded and misfolded proteins, hypoxia, amino acid deprivation, viral infection, and ultraviolet light. It has been known that viral infection can activate ISR, but the role of ISR during viral infection is still unclear. In some cases, ISR is a protective mechanism of host cells against viral infection, while viruses may hijack ISR for facilitating their replication. This review highlighted recent advances on induction of ISR upon viral infection and the downstream responses, such as autophagy, apoptosis, formation of stress granules, and innate immunity response. We then discussed the molecular mechanism of ISR regulating viral replication and how viruses antagonize this cellular stress response resulting from ISR.